How does internal governance affect banks’ financial stability? Empirical evidence from Egypt - Mohamed Marie (14150031) (2022)
This paper investigates whether internal governance mechanisms were associated with the financial stability of Egyptian banks over the period 2010–2019. To this end, a GMM regression analysis was employed using 252 firm-year observations. The results, in general, indicate that the level of banks’ financial stability is positively associated with board size, board meetings, and board gender. In contrast, the results show that board education and the ownership of shares by directors are negatively associated with banks’ financial stability. More interestingly, our results demonstrate that higher financial stability is significantly associated with lower board independence, the presence of CEO duality, and fewer audit committee meetings. These striking results can be attributed to the argument that the presence of independent directors on the board may reduce the CEO’s willingness to share information with board members, causing a high level of uncertainty in the decision-making process, which ultimately leads to a reduction in the financial stability of their bank. Other Information Published in: International Journal of Disclosure and Governance License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1057/s41310-021-00110-8